2017
DOI: 10.1111/pce.12944
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced growth of halophyte plants in biochar‐amended coastal soil: roles of nutrient availability and rhizosphere microbial modulation

Abstract: Soil health is essential and irreplaceable for plant growth and global food production, which has been threatened by climate change and soil degradation. Degraded coastal soils are urgently required to reclaim using new sustainable technologies. Interest in applying biochar to improve soil health and promote crop yield has rapidly increased because of its multiple benefits. However, effects of biochar addition on the saline-sodic coastal soil health and halophyte growth were poorly understood. Response of two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
118
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 246 publications
(134 citation statements)
references
References 68 publications
12
118
1
3
Order By: Relevance
“…These results are consistent with our hypothesis that B and HS enhance soil microbial activity. Zheng et al [24] noticed that B (peanut Shell 350 • C) induced a microbial response in the rhizosphere. Moreover, Bhaduri et al [61] also reported that B application (peanut Shell 300 • C, in 5% dose) on saline soil influenced microbial growth and C use efficiency led to increases in soil microbial biomass.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with our hypothesis that B and HS enhance soil microbial activity. Zheng et al [24] noticed that B (peanut Shell 350 • C) induced a microbial response in the rhizosphere. Moreover, Bhaduri et al [61] also reported that B application (peanut Shell 300 • C, in 5% dose) on saline soil influenced microbial growth and C use efficiency led to increases in soil microbial biomass.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to silicon content, rhizosphere microorganisms may be enhanced by biochar amendment to soils to increase induced defense responses. Many studies indicate that biochar amendment to soils can change the composition of microbial communities in the rhizosphere . In addition, biochar contains a number of organic compounds belonging to various chemical classes, some of which may directly elicit plant defense responses .…”
Section: Discussionmentioning
confidence: 99%
“…We observed that the overall abundances of Actinobacteria , Elusimicrobia , Planctomycetes , Verrucomicrobia , and WCHB1_60 phyla were significantly higher in the rhizosphere with the biochar treatments, whereas only Elusimicrobia was selected at the phylum level in the bulk soils (Figure ). Greater abundance of specific bacterial species (i.e., Proteobacteria , Bacteroidetes , Acidobacteria , and Verrucomicrobia ) was also found in the biochar‐amended rhizosphere soil than those without biochar (Zheng et al, ). Secondly, the responding microbes in the rhizosphere soil were outnumbered than those in the bulk soil, despite the level of taxonomic resolution and number of microbial domains (Figures and ; Table ), indicating that the effects of biochar addition on rhizosphere bacterial community were more evident than those on bulk soil.…”
Section: Discussionmentioning
confidence: 99%